275 Replacing cottonseed meal and sorghum grain with corn dried distillers grains with solubles in lamb feedlot diets: carcass characteristics and sensory panel traits. (5th December 2019) - Hodges, Kade M; Kerth, Chris R; Whitney, Travis R; Ramsey, Wesley S; Wall, Kayley R; Hicks, Zena M; Tucker, Dylan H; Woerner, Dale
Abstract: Carcass and sensory panel traits were evaluated in Dorper ram lambs (n = 46) fed feedlot diets where cottonseed meal (CSM) and sorghum grain were replaced with dried distillers grains with solubles (DDGS). In a randomized design study, lambs were individually fed ad libitum 70.9% concentrate diets for 61 d in individual pens. The positive control diet (CNTL) contained CSM, sorghum grain, and other concentrates, but no DDGS. Four treatment diets were similar to CNTL, but did not contain CSM. Corn DDGS replaced 0% (0DDGS), 33% (33DDGS), 66% (66DDGS) or 100% (100DDGS) of the sorghum grain in the treatment diets. Lambs fed CNTL were contrasted to those fed 0DDGS and linear and quadratic effects were evaluated within the four treatment diets. At 48-h postmortem, the longissimus thoracis was removed from the carcass, frozen, thawed, cooked, and evaluated by a trained sensory panel. Lambs fed CNTL had greater (P ≤ 0.03) hot carcass weight (HCW) and ribeye area (REA) than lambs fed 0DDGS. As DDGS incrementally replaced sorghum grain, HCW and flank fat quadratically increased (P ≤ .05), marbling linearly decreased (P = 0.03), ribeye area tended to linearly increase (P = 0.06), and skeletal maturity tended to linearly decrease (P = 0.06). No differences in sensory characteristics were observed (P ≥ 0.06) between lambs fed CNTL or 0DDGS. As DDGS incrementally replaced sorghum grain, juiciness linearly increased (P = 0.03), cook loss quadratically increased (P = 0.05), lamb flavor identity tended to quadratically increase (P = 0.09) and certain flavor attributes quadratically increased (brown, roasted, umami; P ≤ 0.03), quadratically decreased (metallic; P = 0.004), or linearly increased (bloody; P = 0.003). Results indicated that carcass and sensory characteristics are not negatively affected (some are enhanced) when DDGS replaces CSM and sorghum grain in Dorper lamb feedlot diets.